¿Orfandades de los jóvenes o añoranzas de los mayores? (Journal of Parents and Teachers, 2025)
There are three basic types of orphanhood: motherless, fatherless, and parentless. However, we could say that there are other types of orphanhood, possibly with a more subtle impact, such as children who have a biological mother but no mother present or involved, no father present, attentive or with time to play and witness their child's achievements. There is also the orphanhood of children without parents who live together. In addition to these types of orphanhood, we also find children who are orphaned of achievements through their own efforts, of imagination in their childhood and adolescence, of reading and inner freedom, of times and styles of reflection. With all this, orphanhood is not chosen, it is suffered. Are we adults to blame?
Keywords: orphanhood, absent parents, longing, comfort, lack of reading.